2021
DOI: 10.1111/hel.12814
|View full text |Cite
|
Sign up to set email alerts
|

Acute gastric mucosal lesions caused by acute infection of non‐HelicobacterpyloriHelicobacter: a case report

Abstract: Acute gastric mucosal lesions (AGML) is a typical clinical entity in acute gastritis, and is characterized by severe erosion, hemorrhage, ulceration, or a combination of these.Except in only a few reports, non-Helicobacter pylori Helicobacter (NHPH) infection has not been reported as a cause of AGML. So, at present, NHPH is not widely recognized as a cause of AGML. We report here an extremely rare case of AGML caused by an acute infection of NHPH and discuss when to start eradication therapy. | C A S E REP ORT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…The successful eradication of NHPH infections has recently been achieved by only proton pump inhibitor (PPI) treatment, without the need for antimicrobial agents. 41 In this study, because only an inhibitor of gastric acid secretion was administered, the infected H. suis might not have been entirely eradicated, but merely decreased to a level undetectable by PCR. Alternatively, the bacteria might have been naturally eradicated along with the disease progression.…”
Section: Discussionmentioning
confidence: 89%
“…The successful eradication of NHPH infections has recently been achieved by only proton pump inhibitor (PPI) treatment, without the need for antimicrobial agents. 41 In this study, because only an inhibitor of gastric acid secretion was administered, the infected H. suis might not have been entirely eradicated, but merely decreased to a level undetectable by PCR. Alternatively, the bacteria might have been naturally eradicated along with the disease progression.…”
Section: Discussionmentioning
confidence: 89%
“…NHPH causes infection in the human gastric mucosa, induces gastritis, and is associated with gastric MALT lymphoma. Although acute gastritis and acute gastric mucosal lesions (AGML) caused by NHPH have been reported in previous studies [ 10 12 ], most NHPH infections also cause chronic gastritis without symptoms [ 13 ]. Regarding MALT lymphoma, Stolte et al found it in seven of 202 patients with NHPH gastritis [ 3 ], and Okiyama et al found it in four of 15 patients with NHPH gastritis [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human zoonosis due to NHPH infection has been associated with chronic gastritis, peptic ulcer disease, low-grade MALT lymphoma and gastric cancer. [275][276][277] 2.6.2 Chronic (long-standing) gastritis of specific aetiology is rare and usually represents the phenotypical expression of a condition involving other parts of the gastrointestinal tract. The aetiology can be due to communicable or non-communicable agents and is distinct from gastritis associated with systemic disease.…”
Section: Low-prevalence Gastritis: Preamblementioning
confidence: 99%